The Influence of Village Fund Management on the Village Economy in Southeast Minahasa District - Alvianus K. Sumual; Paulus Kindangen; S. M Engka (International Journal on Economics, Finance and Sustainable Development, 2022)
This study aims to determine the effect of village fund management in this case education and health, infrastructure, and local village economic development, on the village economy in Southeast Minahasa district. The data used in this study is secondary data obtained based on available data and sourced from reports from the Ministry of Villages and Development of Disadvantaged Regions and Transmigration, the Community Empowerment Service of Southeast Minahasa Regency, Southeast Minahasa Regency Regional Finance Agency, and South Minahasa Regency Central Statistics Agency. The data included in this study is the 2016-2020 Village Fund data. This study aims to determine: 1) The effect of the allocation of village funds for education and health on the village economy in Southeast Minahasa Regency; 2) The influence of the allocation of village funds for the construction of facilities and infrastructure on the village economy in Southeast Minahasa Regency. 3) The influence of the allocation of village funds for the development of local economic potential on the village economy in Southeast Minahasa Regency; 4) The effect of the allocation of village funds for education and health, development of facilities and infrastructure and the development of local economic potential together on the village economy in Southeast Minahasa Regency.